1994
DOI: 10.5935/0305-7518.19940022
|View full text |Cite
|
Sign up to set email alerts
|

Eye disease in newly diagnosed leprosy patients in eastern Nepal

Abstract: To determine the magnitude of eye lesions in newly diagnosed leprosy patients we examined their eyes. The Eastern Leprosy Control Project was supported by The Netherlands Leprosy Relief Association; we used the regional clinic in Biratnagar and 5 mobile clinics in surrounding districts as our survey area. All patients who presented at the clinics over 10 weeks, diagnosed as having untreated leprosy were included. Of the 260 examined patients 97 (37,3%, 95% confidence interval 28,3-40'3%) had an eye lesion; 12/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Malla et al (1981) reported 69.8% eye involvement of leprosy in newly diagnosed cases, and this rate was reported as 43.4% by Sehgal et al (1976) and 37.0% by Lubbers et al (1994). The most common finding was madarosis in our study (71.4%).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Malla et al (1981) reported 69.8% eye involvement of leprosy in newly diagnosed cases, and this rate was reported as 43.4% by Sehgal et al (1976) and 37.0% by Lubbers et al (1994). The most common finding was madarosis in our study (71.4%).…”
Section: Discussionmentioning
confidence: 49%
“…Nerve beading was also common (47.6%, 95% CI 25.7-70.2%). Corneal involvement in our newly diagnosed leprosy patients was very high compared to Lubbers' (1994) findings.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…38 A recent study of newly diagnosed leprosy patients in Nepal found 37% prevalence of eye lesions; 4.6% had sight-threatening lesions such as lagophthalmos, iris involvement and corneal anesthesia. 39 Blindness is usually a sequel to corneal lesions (following corneal anesthesia and lagophthalmos) and complicated cataract. 40 B ONES : Chronic osteomyelitis is a feature of the late stage of lepromatous leprosy.…”
Section: Renal Involvementmentioning
confidence: 99%